Using the Picture Word Inductive Model (PWIM) to Write Descriptive Text - Rachel Rachel; Malmy Samban (Universitas Cokroaminoto Palopo, 2022)
To achieve the goal of learning English, the students must know how to write English well. Some of methods that the teacher had used in teaching it. One of the methods can be used in teaching writing descriptive text, namely Picture Word Inductive Model (PWIM).This is the reason of the writers of the research to conduct a research to know the effectiveness of PWIM in teaching writing descriptive text by the eleventh class students of SMA Kristen Makale. The type of research used to achieve the above objective is descriptive quantitative. The data was collected through written test that was given to the students. The total respondents were 20. Result of the research indicates that the mean score of the students in pretest was 51, 68 and falls into bad score classification while the mean score of the post test was 76,5 and falls into good score classification. So, the students’ achievement in writing descriptive text was better after using Picture Word Inductive Model (PWIM). Comparing with the t-test value at the level significance on α 5% (0,05 ) it was higher than t-table with degree freedom (df) = n-1, if found that t-test ( 7,75) value is higher than t-table 17.2913. It can be concluded that Picture Word Inductive Model (PWIM) is effective used in writing descriptive text at the eleventh class students of SMA Kristen Makale.